INTEGRASI TA’DIB ISLAMI DAN TAHFIDZ JUZ 30 DALAM MEMBENTUK KARAKTER RELIGIUS SANTRI AT-TAROJJI - Saifudin; Nur Ariyanti (Rihlah Review: Jurnal Pendidikan Islam, 2025)
This research examines the integration of Islamic ta’dib values and the Juz 30 tahfiz program in developing the religious character of students at Pesantren At-Tarojji. The purpose of this study is to explore how the combination of character education and Qur’anic memorization contributes to shaping students' religiosity, discipline, and moral behavior. Employing a qualitative descriptive method, data were collected through observation, in-depth interviews with musyrifah, teachers, and students, as well as documentation review. The study found that the integration is reflected in structured daily routines, active role modeling by educators, and continuous spiritual mentoring. Tahfiz activities are not limited to memorization but are also used as a medium for internalizing Islamic values contained in the verses. Through reflective learning and consistent practice, students gradually form strong religious habits and personal discipline. The presence of musyrifah in small-group mentoring intensifies students' engagement and helps them apply Islamic values in their daily lives. The holistic approach implemented in this pesantren encourages not only cognitive mastery of the Qur’an but also emotional and behavioral development aligned with Islamic teachings. The findings suggest that integrating ta’dib and tahfiz programs can be a highly effective strategy for building students' religious character in Islamic educational institutions. This study provides insights for educators and pesantren administrators aiming to enhance character formation through Qur’an-centered, value-based education.